THE REALITY OF WOMEN'S EMPOWERMENT IN ALGERIAN SOCIETY. A STUDY OF FACTORS, STRATEGIES AND LEVELS - Radja Bouzidi,; Mustapha Mostefaoui,; Mohammed Benlebbad, (International Journal of Innovative Technologies in Social Science, 2025)
Women's empowerment is crucial for human development, and its promotion, particularly in community development, is a key contemporary Arab issue. Recognised as a fundamental development indicator, comprehensive progress is linked to the participation of both sexes at all levels.This study evaluates Algeria's experience with policies and legislation concerning women's education and employment, examining their impact on women's status and societal roles. Using statistical data, the research explores the levels of women's empowerment in Algeria and discusses the challenges women face within this context.